Aksesibilitas dan Pemanfaatan Aplikasi “ Jogja Smart Service” untuk Mewujudkan Good Governance - Novia Wahyu Indriyani; Rosalia Prismarini Nurdiarti; M. Nastain (Jurnal Riset Public Relations, 2022)
Abstract. The city of Yogyakarta is one of the developing smart city developments. Smart city is an urban service that is carried out by utilizing the role of information technology. This technology-based public service is realized through the “Jogja Smart Service” (JSS) application. From jss.jogjakota.go.id data, currently the number of active users of the "Jogja Smart Service" application is 75,970 out of 210,000 residents of Yogyakarta City. The presence of this application as a form of good governance with integrated information provider technology, making it easier for the public to access information about the development and public services of the City of Yogyakarta in a precise, fast and actual manner. The purpose of this study is to understand and know the process of utilizing and accessing information between the government and the community, to realize a smart city as a pillar for the creation of good governance. The method used in this research is descriptive qualitative, with data collection techniques through observation, in-depth interviews and documentation. The resource persons consisted of four residents of Yogyakarta City from different kelurahan and the Head of the Planning and Implementation Section of the Information Communications and Encryption Service Office of the City of Yogyakarta. From the results of the study, it was found that residents easily access the application and there are skills training features, MSME services, free hotspot services in each RW. It's just that from the aspect of utilization there are still those who do conventional public service administration. On the other hand, the government needs to periodically update information from related agencies. Abstrak. Kota Yogyakarta menjadi salah satu yang mengembangkan pembangunan smart city. Smart city merupakan pelayanan pada aspek – aspek yang menyangkut perkotaan dan dilakukan dengan memanfaatkan teknologi informasi. Pelayanan publik berbasis teknologi tersebut diwujudkan melalui aplikasi “Jogja Smart Service” (JSS). Dari data jss.jogjakota.go.id, saat ini jumlah pengguna aktif aplikasi “Jogja Smart Service” sebesar 75.970 dari 210.000 penduduk Kota Yogyakarta. Hadirnya aplikasi ini sebagai wujud good governance dengan teknologi penyedia informasi yang terintegrasi, sehingga membantu warga untuk mengakses informasi tentang perkembangan dan pelayanan publik Kota Yogyakarta secara tepat, cepat dan aktual. Tujuan dari penelitian ini adalah untuk memahami dan mengetahui proses pemanfaatan dan kedekatan akses informasi antara pemerintah masyarakat, untuk mewujudkan smart city sebagai satu penopang bagi penciptaan good governance. Metode yang digunakan dalam riset ini yaitu deskriptif kualitatif, dengan teknik pengumpulan data melalui observasi, wawancara mendalam dan dokumentasi. Narasumber terdiri dari empat warga Kota Yogyakarta dari kelurahan yang berbeda dan Kepala Seksi Perencanaan dan Implementasi Sistem Informasi Dinas Komunikasi Informatika dan Persandian Kota Yogyakarta. Dari observasi dan eksplorasi data pada penelitian ini diperoleh hasil bahwa warga bisa dengan mudah mengakses aplikasi tersebut dan tersedia fitur- fitur pelatihan ketrampilan, pelayanan UMKM, layanan free hotspot di setiap RW. Hanya saja dari aspek pemanfaatan masih ada yang melakukan administrasi pelayanan publik secara konvensional. Di sisi lain pemerintah perlu memperbaharui secara berkala informasi-informasi dari dinas terkait.